Metaphors of the Pandemic Through the Lenses of the Bulgarian Parliament - Petya Osenova (Slavia Meridionalis, 2025)
This paper presents a corpus survey on metaphor types in a contemporary Bulgarian corpus of Parliamentary Sessions. The following processes are described: the extraction of the contexts of the selected key words virus, coronavirus, pandemic, epidemic, COVID-19, COVID, corona; the classification method that was employed for dividing the detected contexts into the relevant metaphor frames; the language expressions that are associated with the corresponding metaphor type; the frequency of the used key words and the frequency of the related metaphor frames. Some problems are outlined with respect to this kind of study. The most frequent metaphor frames in our data turned out to be CONTROL and WAR.